Changes in attitudes and behaviors supportive of maternal and newborn health in Ethiopia: an evaluative case study - William T. Story; Yared Amare; Lara M.E. Vaz; Heather Gardner; Halkeno Tura; Gail Snetro; Mary V. Kinney; Steve Wall; Abeba Bekele (BMC, 2021)
Abstract Background Ethiopia's high neonatal mortality rate led to the government's 2013 introduction of Community-Based Newborn Care (CBNC) to bring critical prevention and treatment interventions closer to communities in need. However, complex behaviors that are deeply embedded in social and cultural norms continue to prevent women and newborns from getting the care they need. A demand creation strategy was designed to create an enabling environment to support appropriate maternal, newborn, and child health (MNCH) behaviors and CBNC. We explored the extent to which attitudes and behaviors during the prenatal and perinatal periods varied by the implementation strength of the Demand Creation Strategy for MNCH-CBNC. Methods Using an embedded, multiple case study design, we purposively selected four kebeles (villages) from two districts with different levels of implementation strength of demand creation activities. We collected information from a total of 150 key stakeholders across kebeles using multiple qualitative methods including in-depth interviews, focus group discussions, and illness narratives; sessions were transcribed into English and coded using NVivo 10.0. We developed case reports for each kebele and a final cross-case report to compare results from high and low implementation strength kebeles. Results We found that five MNCH attitudes and behaviors varied by implementation strength. In high implementation strength kebeles women felt more comfortable disclosing their pregnancy early, women sought antenatal care (ANC) in the first trimester, families did not have fatalistic ideas about newborn survival, mothers sought care for sick newborns in a timely manner, and newborns received care at the health facility in less than an hour. We also found changes across all kebeles that did not vary by implementation strength, including male engagement during pregnancy and a preference for giving birth at a health facility. Conclusions Findings suggest that a demand creation approach-combining participatory approaches with community empowering strategies-can promote shifts in behaviors and attitudes to support the health of mothers and newborns, including use of MNCH services. Future studies need to consider the most efficient level of intervention intensity to make the greatest impact on MNCH attitudes and behaviors.